HUBUNGAN ANTARA ASERTIVITAS DENGAN PROKRASTINASI AKADEMIK DALAM MENYELESAIKAN SKRIPSI PADA MAHASISWA PROGRAM STUDI PG PAUD ANGKATAN 2012 FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Rizka, Rahmi; Indarto, Wusono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine whether there is a relationship between assertiveness with academic procrastination in completing the thesis on early childhood education Program students the Faculty of Education University of Riau. This research is quantitative research type of correlation. The research method is a survey method is a method of research that uses data collection technique is done through a questionnaire (questionnaire) to assertiveness and academic procrastination. Samples were determined in this study amounted to 41 students. Data analysis technique using the formula Pearson product moment then do a t-test with the help of IBM SPSS Ver.20 Statistick. There is a significant relationship between assertiveness with academic procrastination students of the Faculty of Early Childhood Education at the University of Riau correlation coefficient of r xy = 0.375, p = 0.016, where p <0.05. That assertiveness contributed only 14.06% of the students' academic procrastination in completing the thesis that are in a weak category. Was to prove a hypothesis test based on the calculation results obtained thitung 2,526 while the value table = 2.021. t hitung > t table (2.526 > 2.021) Then Ho is rejected and Ha received means that there is a significant correlation between the two variables.Keywords: assertiveness, academic procrastination